Age and social experience induced plasticity across brain regions of the paper wasp Polistes fuscatus. (14th April 2021) - Jernigan, Christopher M.; Zaba, Natalie C.; Sheehan, Michael J.
Abstract : Developmental studies of brain volumes can reveal which portions of neural circuits are sensitive to environmental inputs. In social insects, differences in relative investment across brain regions emerge as behavioural repertoires change during ontogeny or as a result of experience. Here, we test the effects of maturation and social experience on morphological brain development in Polistes fuscatus paper wasps, focusing on brain regions involved in visual and olfactory processing. We find that mature wasps regardless of social experience have relatively larger brains than newly emerged wasps and this difference is driven by changes to mushroom body calyx and visual regions but not olfactory processing neuropils. Notably, social wasps invest more in the anterior optic tubercle (AOT), a visual glomerulus involved in colour and object processing in other taxa, relative to other visual integration centres the mushroom body calyces compared with aged socially naive wasps. Differences in developmental plasticity between visual and olfactory neuropil volumes are discussed in light of behavioural maturation in paper wasps, especially as it relates to social recognition. Previous research has shown that P. fuscatus need social experience to develop specialized visual processing of faces, which is used to individually recognize conspecifics. The present study suggests that the AOT is a candidate brain region that could mediate facial processing in this species.